EFISIENSI HUNIAN TEMPAT TIDUR DENGAN KEJADIAN HA’Is PADA MASA PANDEMI COVID-19 DI RSUD HARAPAN DOA KOTA BENGKULU - Nofri Heltiani (Politeknik Kesehatan Kemenkes Malang, 2021)
Background: The efficiency of inpatient bed occupancy is something that must be considered in hospital quality. To determine the efficiency pf bed occupancy, a bed occupation rate indicator is needed, averate length of stay, turn over interval and bed turn over. The decline in the number of patient visits during the covid 19 pandemic period will affect the use of beds, hai’s and cost received by the hospital. Subjects and Method: The type of research used is analytic with a cross sectional approach. The sample in this study used a total population of 2.155 patients who were analyzed univariate. Results: Indicator value in the safa room obtained BOR 65,56%, AvLOS 2,81 days, TOI 12,68 days and BTO 39,11 times. Marwah room obtained BOR 51,01%,AvLOS 2,80 days,TOI 19,92 days,BTO 24,54 times and Mina room obtained BOR 90,15%,AvLOS 2,67 days,TOI 7,43 days and BTO 33,14 times. This indicates that the efficiency. Of Bed Occupancy in the there inpatient rooms is not efficient and is supported by a result 0% hai’s value. Conclusion:It is necessary to increase kwonledge about illness and disease that can be overcome by effective promotion of hospital public health.